Characteristic Model-Based Robust Model Predictive Control for Hypersonic Vehicles with Constraints - Zhang, Jun; Sun, Tairen; Pan, Yongping (Frontiers in Robotics and AI, 2017)
Designing robust control for hypersonic vehicles in reentry is difficult, due to the features of the vehicles including strong coupling, nonlinearity, and multiple constraints. This paper proposed a characteristic model-based robust model predictive control (MPC) for hypersonic vehicles with reentry constraints. Firstly, the hypersonic vehicle is modeled by a characteristic model composed of a linear time-varying system and a lumped disturbance. Then, the identification data are regenerated by the accumulative sum idea in the grey theory, which weakens effects of the random noises and strengthens regularity of the identification data. Based on the regenerated data, the time-varying parameters, and the disturbance are on-line estimated according to the grey identification. At last, the mixed H2/H∞ robust predictive control law is proposed based on linear matrix inequalities(LMI) and receding horizon optimization techniques. Using active tackling system constraints of MPC, the input and state constraints are satisfied in the closed-loop control system. The validity of the proposed control is verified theoretically according to Lyapunov theory and illustrated by simulation results.